(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2022)
Purpose: The paper discusses the role and importance of smart governance as a modern form of urban development, identifies the key determinants of smart governance, analyzes models, evaluation and measurement indicators in smart and sustainable cities, and ranks 127 Croatian cities, regardless of city size. Methodology: A comprehensive database was prepared for the preparation of the study, including ten indicators of key smart governance determinants related to political participation of citizens, delivery of quality services to citizens, and sustainable functioning of city administration, in line with a review of models and indicators from previous studies. Results: The main goal of this research is to determine a correlation between the size of the city according to the number of inhabitants and statistically significant indicators of smart governance and, based on the value of the correlation coefficients, to determine the weights for the indicators in the process of city ranking. By aggregating the weighted z-scores, the Smart Governance Index was created for all Croatian cities and that index is not related to the size of a city. Conclusion: Statistically significant indicators for the formation of the Smart Governance Index for 127 cities in Croatia are the indicators of political participation and sustainable functioning of city administration. It is necessary to include as many indicators as possible in the future period so that the ranking results are as relevant as possible.